USE OF PSYCHOACTIVE DRUGS AMONG MEDICAL UNDERGRADUATES IN ABBOTTABAD - Nawaz, Haq; Khan, Aftab Alam; Bukhari, Saima (Journal of Ayub Medical College Abbottabad, 2017)
Background: Psychoactive substance abuse is prevalent among medical undergraduates of Pakistan, India & Western countries which can adversely affect the physical & psychological grooming of a medical undergraduate thus threatening to compromise their role as future physicians & health-care providers in the society. The objective of the present cross-sectional study was to explore the prevalence and patterns of psychoactive substance/drug consumption among undergraduate students of a public sector medical college in Abbottabad. Methods: Seven hundred and eighty participants after informed consent were requested to fill a questionnaire seeking information about their demographics, patterns & behaviours regarding ten common psychoactive substances of abuse including (Cigarettes, Benzodiazepines, naswar, cannabis, alcohol, amphetamine, opium, cocaine, heroin & organic solvents). Results: Overall students who responded were 698 (89.48%). One hundred and fifty (21.49%) admitted to the use of a psychoactive substance in past or at present. Majority users (71.33%) were males. Overall (81.33%) users were living in hostel or a rented apartment. Substance abuse was more prevalent among senior students, i.e., 30.06% & 24.24% in 4th year & final year MBBS respectively. Majority of the consumers, i.e., 93 (62%) were falling in an age group between 15-20 years. Main reasons behind substance abuse were: psychological stress (49.33%) and pleasure seeking (42.67%). Substances/drugs used by students in order of preference were Cigarettes 115 (76.67%), Benzodiazepines 48 (32%), naswar 42 (28%), Cannabis 41 (27.33%), Alcohol 24 (16%), Amphetamine 22 (14.67%), Opium 15 (10%), Cocaine 14 (9.33%), Heroin 11 (7.33%) & Organic solvents 05 (3.33%). Use of more than one substance was observed in 70 (46.67%) students. Conclusion: It is concluded that prevalence of cigarette smoking, naswar, benzodiazepines, cannabis & alcohol is high among medical undergraduates in Abbottabad which is a matter of concern. Efforts are needed to create better awareness among them about the hazards of substance abuse on their health, upcoming professional career and ailing humanity under their care. Keywords: Pakistan, Psychoactive substance abuse; Psychoactive drug abuse; Medical students; Medical undergraduates